Better Together: Conditions for Sustainable Innovation Aimed at Improving Quality of Care in Health Delivery Organizations - Kievit, Pieter J. (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The resilience of health care organizations over time in a changing and ever challenging socio-economic environment depends on effective innovation. Innovation is based on translating research outcomes into interventions aiming at improving quality of care which is defined as a combination of six dimensions: effectiveness, efficiency, safety, equity, accessibility and patient-centeredness of care. The majority of research papers on innovation and quality improvement deal with the conditions for dissemination and implementation (D&I) but does not address the conditions for long term valorisation of research outcomes or adopting them beyond the implementation period. Factors determining successful D&I are ordered in frameworks consisting of five domains: characteristics of the intervention, internal context, external context, adopters skills and design and management of the implementation process. In general, these frameworks provide a descriptive tool or taxonomy, but miss explanatory power which will eventually be found in a theory of good decisional practice.